Diagnosing Students’ Problem-Solving Challenges in Rotational Dynamics Using Two-Tier AR Flashcard Tests - Isnaini, Fiqran; Maria Silitonga , Haratua Tiur; Syarif Hidayatullah, M. Musa; Sirait, Judyanto; Afrizon, Renol (Jurnal Inovasi Pendidikan IPA, 2025)
The inadequate capacity of students to recognize and resolve difficulties, particularly with intricate concepts, has emerged as a significant concern in physics education. This project aims to develop a two-tier diagnostic assessment that utilizes augmented reality (AR) flashcards to identify students' challenges in problem-solving. This media-assisted assessment aims to visually represent concepts interactively while examining students' comprehension and the origins of their challenges. The study methodology employs the ADDIE development paradigm, encompassing analysis, design, development, implementation, and evaluation. Validation is performed by subject matter and media specialists, subsequently followed by trials with secondary education students. The study equipment comprises validation sheets, answer questionnaires, and diagnostic examinations supplemented by augmented reality flashcards. The study demonstrates that the two-tier diagnostic test augmented with AR flashcards effectively identifies students' challenges, particularly in grasping concepts and problem-solving processes, as indicated by a Cronbach's alpha reliability coefficient of 0.89. This media-assisted assessment enhances student engagement, as evidenced by survey findings indicating that students perceive it as easier to comprehend physics concepts through the instrument. This research is anticipated to motivate educators and institutions to create more creative AR-based learning media for evaluations and interactive learning